Evolution of non-collinear magnetic state of exchange biased ferromagnet/normal metal/ ferromagnet/superconductor heterostructure in magnetic field studied by polarized neutron reflectometry - Khaydukov, Yu.; Morari, R.; Zdravkov, V.; Mustafa, L.; Keller, T.; Keimer, B.; Sidorenko, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
By using waveguide enhanced polarized neutron reflectometry we have characterized the magnetic state of exchange biased CoOx(20 nm)/Co(4 nm)/Nb(5 nm)/Co(2 nm)/Nb(25 nm)/Al2O3 system. Measurement allowed to determine the dependence of the inclination angles of magnetic moment of the both Co layers as a function of applied field. According to the measurement the soft Co(2 nm) layer magnetization turns towards external field in magnetic fields as small as 20 Oe. In contrast direction of magnetic moment of Co(4 nm) layer can not be altered in magnetic fields as high as 2 kOe.